Black supplementary school leaders: Community leadership strategies for successful schools. (October 2020) - Maylor, Uvanney
Long established in the United Kingdom, Black supplementary schools are valued by Black parents for their ability to nurture the academic potential of Black students and achieve positive educational outcomes where mainstream schools sometimes fail. Through exploratory qualitative interviews conducted with a small group of African-Caribbean supplementary school leaders, this article seeks to understand Black supplementary school leaders' perceptions of educational leadership and supplementary school success. Utilising Yosso's perspective on 'community cultural wealth', in particular the ways in which Black communities provide and are rich in cultural/educational resources, the article examines the extent to which the leadership perceptions of Black supplementary school leaders are rooted in notions of community and serving, along with the leadership strategies they employ in creating successful schools. Such insights are especially important at a time when mainstream education continues to deliver poor educational outcomes for Black students.